THE EXPLOITATION OF MOTIVATIONAL STRATEGIES IN TEACHING SPEAKING BY FOURTH-YEAR STUDENTS IN THEIR TEACHING PRACTICUM AT ENGLISH DIVISION I : A MULTI-CASE STUDY AT FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, ULIS-VNUH - Trần, Đức Phương Anh (2020)
The role of motivation in language learning and of applying motivational strategies in language teaching as well as the fact that it is difficult for young teachers, especially student-teachers to successfully employ those motivational strategies in their classes have become a great incentive for the researcher to conduct this research paper. The researcher aims at firstly, figuring out how many motivational strategies the student-teachers know in teaching speaking; then secondly, the study is conducted to examining what motivational strategies are considered effective in stimulating first-year students’ attention and participation as perceived by both the student-teachers and the first-year students.